Drought‐Induced Soil Desiccation Cracking Behavior With Consideration of Basal Friction and Layer Thickness. Issue 7 (29th June 2020) - Zeng, Hao; Tang, Chao‐Sheng; Cheng, Qing; Zhu, Cheng; Yin, Li‐Yang; Shi, Bin
Abstract: Drought‐induced cracking of soils is of great concern with the advent of global climate change. The cracking process accelerates the evaporation rate of pore water, lowers the water retention capacity, and degrades the hydraulic‐mechanical properties of soils. Basal friction and layer thickness are two important aspects affecting the subsurface cracking. To explore their detailed effects on soils under drying, we conduct a series of desiccation tests on twelve slurry soil bars and select four types of base materials with different roughness levels and three kinds of layer thicknesses. We track the dynamic cracking process in various samples and adopt the noncontact optical technique—digital image correlation—for the motion of soil particles. Experimental results validate that the coupled effects of basal conditions and soil layer thickness play a key role in governing the soil cracking behavior. The presence of rough bottom surface induces the onset and propagation of desiccation cracks at both top and bottom surfaces. Some of the cracks initiated at the bottom do not propagate through the soil profile. Increasing layer thickness weakens the effect of basal friction on the soil top surface shrinkage but increases the frictional force acting on the base and results in more crack initiations at the bottom. The digital image correlation results further reveal that cracks initiated on the bottom surface and propagated upward vertically are dominated by tensile stresses, while those propagated upward obliquely are dominated by the joint action of shear and tensile stresses. Key Points: Soil desiccation cracking significantly depends on both basal boundary condition and soil layer thickness Desiccation cracks initiate not only at soil top surface but also at bottom, which is strongly associated with the basal roughness level Cracking on top surface is governed by tensile stresses; cracking on bottom surface is governed by coupling of shear and tensile stresses